A rare case of double cervix with normal uterus and vagina: Müllerian anomaly in North India - Jasmine,; Bains, Sunil S.; Tanya, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Bifid cervix is a rare Müllerian duct anomaly. We present a case of a 38-year-old woman with secondary infertility, found to have a cervical duplication. To the best of our knowledge, only a few cases of bicervical normal uterus with normal vagina exist in the literature. This form of uterine abnormality is not explicable by the existing classical theory of Müllerian anomalies and suggests that a complex interplay of events beyond the classical postulate gives rise to the female genital tract.